Microstructure and properties of solid-state additive manufactured Mg–10Li–3Al–3Zn magnesium alloy - Jie Yao; Guoqing Dai; Yanhua Guo; Wenya Li; Zhonggang Sun; Zhikang Shen; Kaiyu Luo; Hui Chang; Lian Zhou (Journal of Materials Research and Technology, 2023)
A comprehensive investigation of friction stirring additive manufacturing (FSAM) Mg–10Li–3Al–3Zn alloy has been conducted to evaluate microstructure evolution and mechanical properties. The results indicated that new intermetallic compounds of Li2MgAl and LiMgZn are precipitated. The microstructure homogeneity is improved and the texture strength of [−1100] is decreased via FSAM. Compared to the base metal, the microhardness of nugget zone has increased by 33%, and the tensile strength of the samples along transverse direction and process direction are 206 MPa and 224 MPa, respectively. The strengthen mechanism of mechanical properties also has been analyzed through phase distribution and grain refinement. The study reveals that FSAM is a significant approach for the additive manufacturing magnesium alloys.